ANALISIS PEMBENTUKAN KERAK DI DALAM PIPA PDAM SEMARANG - Titis Septianna Sari; Athanasius Priharyoto Bayuseno (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Pipes are important components in a system drinking water to transport water flow. If one of the pipes experiences corrode and scaling, the potential economic losses will be high. To determine the scale formation and corrosion in the pipeline of PDAM Semarang tests was performed including: Chemical Composition Test, Hardness Test, Piping Material Microstructure, SEM-EDX Test and Test XRD. The test results show that the pipe of PDAM Semarang can be classifield as the low carbon steel according to material type